DAVID BATHRICK, BRAD PRAGER, and MICHAEL D. RICHARDSON, eds., Visualizing the Holocaust: Documents, Aesthetics, Memory - Scheinberg, Ellen (Archivaria, 2014)
Visualizing the Holocaust: Documents, Aesthetics, Memory. DAVID BATHRICK, BRAD PRAGER, and MICHAEL D. RICHARDSON, eds. Rochester, NY: Camden House, 2008. vi, 336 pp. ISBN 978-1-57113-542-1.